2002
DOI: 10.1093/brain/awf248
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical band heterotopia (SBH) in males: clinical, imaging and genetic findings in comparison with females

Abstract: Subcortical band heterotopia (SBH) or double cortex syndrome is a neuronal migration disorder, which occurs very rarely in males: to date, at least 110 females but only 11 in males have been reported. The syndrome is usually associated with mutations in the doublecortin (DCX) (Xq22.3-q23) gene, and much less frequently in the LIS1 (17p13.3) gene. To determine whether the phenotypic spectrum, the genetic basis and genotype-phenotype correlations of SBH in males are similar to those in females, we compared the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 66 publications
6
76
0
2
Order By: Relevance
“…The inversion recovery sequence was considered useful for the demonstration of heterotopic gray matter and the assessment of cortical thickness as it provides a strong contrast between gray and white matter. A similar frequency and MRI appearance has been reported in the literature [1][2][3][4][5] . SEH is characterized by periventricular nodules adjacent to the lateral ventricular walls just beneath and abutting the ependyma giving the nodular ventricular wall, and is not enhanced after intravenous contrast administration.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The inversion recovery sequence was considered useful for the demonstration of heterotopic gray matter and the assessment of cortical thickness as it provides a strong contrast between gray and white matter. A similar frequency and MRI appearance has been reported in the literature [1][2][3][4][5] . SEH is characterized by periventricular nodules adjacent to the lateral ventricular walls just beneath and abutting the ependyma giving the nodular ventricular wall, and is not enhanced after intravenous contrast administration.…”
Section: Discussionsupporting
confidence: 85%
“…They do not contain blood vessels or CSF. The thicker the band of heterotopic neurons; the worse the disability and increased prevalence of developmental delay [1,4,9] . In the present study, MRI showed band heterotopia in three females.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SBH is generally associated with defects in the DCX gene, a posterior-toanterior grade of severity has been associated with LIS1 mutations. 11,15 This group of patients was also found not to have deletions or duplications of the DCX gene.…”
Section: Resultsmentioning
confidence: 71%
“…These women may have mild or no intellectual deficits and partial or focal epilepsy. Affected males typically have a more severe brain malformation, such as lissencephaly (smooth brain without sulcal markings) associated with severe mental handicap and West syndrome (7). Therefore, defining the brain malformation that underlies a child's epilepsy may have implications for other family members.…”
Section: Brain Imaging/ Magnetic Resonance Imagingmentioning
confidence: 99%